A new perspective of lactatogenesis by isolated adipocytes. (1st December 2019) - Borghi, Filipy; Morais, Camila L.; Silva, Carolina; da Silva, Priscila C.; Ishizu, Larissa Y.; Costa, Gustavo T.; Grassi-Kassisse, Dora M.
Abstract: Increased adipose tissue mass exhibited greater capacity of glucose transformation in lactate, highlighting lactatogenesis as a crucial factor in body size. Classically, lactate produced by isolated adipocytes are expressed per million of cells and were never correlated with their size. Spontaneously hypertensive rats (SHR) have a lower body weight and smaller adipocytes when compared to Wistar-Kyoto. We evaluated basal lactate by epididymal 15 - weeks-old isolated adipocytes of SHR, Wistar-Kyoto and Wistar. Basal lactate was similar when expressed by one million cells. However, SHR adipocytes were smaller, so we adjusted the results by cell volume and SHR showed higher basal lactate production which was directly endorsed by hyperlactatemia in the presented conditions. Thereby, we suggest a new perspective on lactatogenesis analysis by adipocytes, which could be linked to the receptors density and associate enzymes. Moreover, we showed that the thin and hypertensive rats can be hyperlactemic in fasting conditions. Highlights: Basal lactate was similar when expressed by one million cells. Lactate adjusted by volume exhibited different result. SHR showed higher lactate production by adipocyte volume. SHR exhibited hyperlactatemia under fasting conditions.